Metal-Nx active center catalyst, preparation method thereof and hydrogenation reaction
By supporting the precious metal to the g-C3N4 support, a noble metal-Nx active center catalyst is formed, which solves the problem of activity loss of traditional catalysts in the hydrogenation reaction, and achieves efficient catalytic performance and long service life.
Patent Information
- Application Number
- CN202311369365.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
Smart Images

Figure CN119857512A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogenation catalysts, and in particular to a metal-N x Active center catalyst, preparation method thereof and hydrogenation reaction. Background Art
[0002] Zero-valent noble metal catalysts show excellent catalytic performance in hydrogenation reactions, but traditional zero-valent noble metal catalysts face the problem of active component agglomeration and loss during the reaction, resulting in decreased catalytic performance. Therefore, it is imperative to design and prepare a stable Pd-based active center.
[0003] There are lone pairs of electrons in the outermost structure of the N atom, which can combine with the empty orbitals in the metal electronic structure to form a stable metal-N x In the field of heterogeneous catalysis, Fe-N x and Co-N x Other metals-N x The active components show excellent performance in electrocatalytic reactions. x However, there are few reports on the application of active centers in traditional heterogeneous catalytic reactions.
[0004] Therefore, it is necessary to provide a metal-N x Active center catalyst, used in heterogeneous catalytic reactions with good catalytic activity. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a metal-N x Catalyst, by loading the noble metal onto the carrier, forms a noble metal-N x The present invention also provides a metal-N x A method for preparing a catalyst and a hydrogenation reaction.
[0006] The first aspect of the present invention provides a metal-N x The catalyst comprises a carrier and a noble metal loaded on the carrier, wherein the carrier is g-C3N4, and the catalyst contains a noble metal-N x Active center.
[0007] The metal-N of the present invention x The exposed N atoms in the catalyst carrier undergo electron transfer with the active metal to form metal-N x Active center, metal-N xThe catalytic activity of the active center is much higher than that of zero-valent metals. In addition, the exposed defect sites in the carrier can interact strongly with the metal active center, which greatly avoids the loss of activity during the reaction and prolongs the service life of the catalyst.
[0008] According to some embodiments of the present invention, the noble metal is one or more of Pt, Pd, Ru, Ag, and Rh.
[0009] According to some embodiments of the present invention, the loading amount of the noble metal is 0.5 to 5 wt % of the total mass of the catalyst, preferably 0.8 to 1.2 wt %.
[0010] According to some embodiments of the present invention, the method for preparing the catalyst comprises mixing dicyandiamide and a metal oxide and / or metal salt precursor, calcining the mixture to prepare a carrier, and then loading the noble metal onto the carrier.
[0011] A second aspect of the present invention provides a metal-N x The method for preparing a catalyst comprises the following steps:
[0012] (1) mixing a metal oxide and / or metal salt precursor with a dicyandiamide solution and calcining to obtain a powder;
[0013] (2) contacting the powder obtained in step (1) with an acid solution or an alkali solution to obtain a carrier;
[0014] (3) Loading the noble metal on the carrier to obtain a metal-N x catalyst.
[0015] The preparation method of the catalyst of the present invention comprises selecting a metal oxide as a hard template agent, mixing with a dicyandiamide precursor, and calcining the obtained carrier to fully expose the N site, and to better load the noble metal onto the carrier to form a metal-N x Active center, the catalyst has good catalytic performance in hydrogenation reaction.
[0016] In step (2) of the present invention, the metal oxide or metal salt precursor is contacted with an acid solution or an alkaline solution according to the type of the metal oxide or metal salt precursor, in order to remove the metal oxide.
[0017] According to some embodiments of the present invention, in step (1), the solvent of the dicyandiamide solution is water, thereby avoiding the pollution of the environment by organic solvents.
[0018] According to some embodiments of the present invention, the molar ratio of dicyandiamide to the metal oxide or metal salt precursor is (100-400):1.
[0019] According to some embodiments of the present invention, the metal oxide is selected from one or more of MoO3, WO3, ZnO, MnO2, SiO2, and TiO2.
[0020] According to some embodiments of the present invention, the metal salt precursor is preferably one or more of ammonium molybdate, ammonium tungstate, and zinc acetate.
[0021] According to some embodiments of the present invention, in step (2), MoO3 is removed with NH3H2O, WO3 is removed with NaOH, and ZnO is removed with HCl.
[0022] According to some embodiments of the present invention, after the metal oxide or metal salt precursor is mixed with the dicyandiamide solution, water is removed by rotary evaporation, and after drying for 10 hours, the mixture is transferred to a muffle furnace for calcination.
[0023] According to some embodiments of the present invention, in step (1), the mixing time is 0.5 to 2 hours and the temperature is 40 to 60°C.
[0024] According to some embodiments of the present invention, the calcination conditions include: a calcination temperature of 400 to 600° C., a calcination time of 3 to 5 hours, and a heating rate of 2 to 10° C. / min.
[0025] According to some embodiments of the present invention, in step (2), the pH value of the acid solution is 2-4, or the pH value of the alkali solution is 8-10.
[0026] According to some embodiments of the invention, the acid solution is selected from dilute HCl.
[0027] According to some embodiments of the present invention, the alkali solution is selected from one or more of ammonia water and NaOH solution.
[0028] According to some embodiments of the present invention, in step (3), the precious metal is loaded by impregnation, preferably by equal volume impregnation or excess impregnation.
[0029] According to some embodiments of the present invention, the impregnation method comprises mixing a noble metal salt solution with a carrier, and then adding a reducing agent for reduction.
[0030] According to some embodiments of the present invention, the noble metal is metal nanoparticles.
[0031] The third aspect of the present invention provides a hydrogenation reaction, wherein the hydrogenation reaction is carried out under the catalysis of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect.
[0032] According to some embodiments of the present invention, the hydrogenation reaction is the hydrogenation of nitrobenzene to prepare aminobenzene.
[0033] According to some embodiments of the present invention, the conditions of the hydrogenation reaction include:
[0034] The reaction temperature is 25-35°C, the reaction time is 0.8-1.2h, and the reaction pressure is 0.98-0.12MPa;
[0035] Preferably, the reaction temperature is 30° C., the reaction time is 1 h, and the reaction pressure is normal pressure.
[0036] The present invention is to design and synthesize the precious metal-N x Active species, metal oxides are selected as hard templates and mixed with dicyandiamide, calcined, and then the templates are removed by corresponding acid / base washing to fully expose the N sites in g-C3N4, and then the noble metal nanoparticles are loaded on the g-C3N4 carrier by impregnation. Compared with directly calcining dicyandiamide to prepare g-C3N4 carrier, the template method can expose more N sites, which is beneficial to the noble metal-N x The formation of species.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) Metal-N of the present invention x The active center catalyst can be used as a hydrogenation reaction catalyst. When the precious metal loading is less than 1wt%, the conversion rate of nitrobenzene series can still reach more than 99%, which is much better than the catalytic performance of zero-valent metals under the same reaction conditions.
[0039] (2) The catalyst of the present invention uses dicyandiamide as a precursor and a metal oxide as a template. Compared with directly calcining dicyandiamide to prepare a g-C3N4 carrier, the template method can expose more N sites, which is conducive to the loading of noble metal nanoparticles on the carrier to form noble metal-N x Active center. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the X-ray photoelectron spectrum of the catalyst provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the present invention more easily understood, the present invention will be described in detail below in conjunction with embodiments. These embodiments are only for illustration and are not intended to limit the application scope of the present invention.
[0042] In the present invention, dicyandiamide was purchased from Aladdin Biochemical Technology Co., Ltd., analytically pure; CAS No. 461-58-5;
[0043] MoO3 was purchased from Aladdin Biochemical Technology Co., Ltd., analytical grade; CAS number is 1313-27-5;
[0044] WO3 was purchased from Aladdin Biochemical Technology Co., Ltd., analytical grade; CAS number is 1314-35-8;
[0045] ZnO was purchased from Aladdin Biochemical Technology Co., Ltd., analytical grade; CAS number is 1314-13-2;
[0046] Ammonium molybdate was purchased from Aladdin Biochemical Technology Co., Ltd., analytical grade; CAS number is 13106-76-8;
[0047] Palladium chloride was purchased from MacLean Biochemical Technology Co., Ltd., analytical grade; CAS number is 7647-10-1;
[0048] Ruthenium chloride was purchased from MacLean Biochemical Technology Co., Ltd., analytical grade; CAS number is 14898-67-0;
[0049] Platinum chloride was purchased from MacLean Biochemical Technology Co., Ltd., analytical grade; CAS number is 13454-96-1;
[0050] NaBH4 was purchased from MacLean Biochemical Technology Co., Ltd. with analytical grade; CAS number is 15681-89-7.
[0051] Example 1
[0052] Preparation of MoO3 / g-C3N4: 34 mg of MoO3 and 4 g of dicyandiamide were added to a beaker containing 30 mL of deionized water, and the beaker was placed in a 50°C water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80°C until the water was completely removed to obtain a solid, and then the solid was dried in a 70°C oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and the temperature was increased to 500°C at a heating rate of 5°C / min and kept constant for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named MoO3 / g-C3N4.
[0053] Preparation of g-C3N4(MoO3): Take 4mL of 25wt.% NH3·H2O and dissolve it in 20mL of distilled water. Grind the MoO3 / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove MoO3, then centrifuge and dry. The obtained yellow powder is named g-C3N4(MoO3).
[0054] Preparation of catalyst Pd / g-C3N4(MoO3): Pd nanoparticles were loaded on the prepared g-C3N4(MoO3) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(MoO3) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PdCl2 ammonia solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PdCl2 was reduced to Pd under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pd / g-C3N4(MoO3).
[0055] Example 2
[0056] Preparation of WO3 / g-C3N4: 55 mg WO3 and 4 g dicyandiamide were added to a beaker containing 30 mL deionized water, and the beaker was placed in a 50°C water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80°C until the water was completely removed to obtain a solid, and then the solid was dried in a 70°C oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and the temperature was increased to 500°C at a heating rate of 5°C / min and kept constant for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named WO3 / g-C3N4.
[0057] Preparation of g-C3N4(WO3): Take 4mL of 25wt.% NaOH solution and dissolve it in 20mL of distilled water. Grind the WO3 / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove WO3, then centrifuge and dry. The obtained yellow powder is named g-C3N4(WO3).
[0058] Preparation of catalyst Pd / g-C3N4(WO3): Pd nanoparticles were loaded on the prepared g-C3N4(WO3) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(WO3) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PdCl2 ammonia solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PdCl2 was reduced to Pd under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pd / g-C3N4(WO3).
[0059] Example 3
[0060] Preparation of ZnO / g-C3N4: 20 mg ZnO and 4 g dicyandiamide were added to a beaker containing 30 mL deionized water, and the beaker was placed in a 50°C water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80°C until the water was completely removed to obtain a solid, and then the solid was dried in a 70°C oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and the temperature was increased to 500°C at a heating rate of 5°C / min and kept constant for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named ZnO / g-C3N4.
[0061] Preparation of g-C3N4(ZnO): Take 4mL of dilute HCl (concentration of 1 mol / L) and dissolve it in 20mL of distilled water. Grind the ZnO / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove ZnO, then centrifuge and dry. The obtained yellow powder is named g-C3N4(ZnO).
[0062] Preparation of catalyst Pd / g-C3N4(ZnO): Pd nanoparticles were loaded on the prepared g-C3N4(ZnO) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(ZnO) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PdCl2 ammonia solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PdCl2 was reduced to Pd under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pd / g-C3N4(ZnO).
[0063] Example 4
[0064] Preparation of MoO3 / g-C3N4: 34 mg MoO3 and 4 g dicyandiamide were added to a beaker containing 30 mL deionized water, and the beaker was placed in a 50°C water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80°C until the water was completely removed to obtain a solid, and then the solid was dried in a 70°C oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and the temperature was increased to 500°C at a heating rate of 2°C / min and kept constant for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named MoO3 / g-C3N4.
[0065] Preparation of g-C3N4(MoO3): Take 4mL of 25wt.%NH3•H2O and dissolve it in 20mL of distilled water. Grind the MoO3 / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove MoO3, then centrifuge and dry. The obtained yellow powder is named g-C3N4(MoO3).
[0066] Preparation of catalyst Ru / g-C3N4(MoO3): Ru nanoparticles were loaded on the prepared g-C3N4(MoO3) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(MoO3) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L RuCl3 aqueous solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that RuCl3 was reduced to Ru under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The black powder obtained by centrifugation was named Ru / g-C3N4(MoO3).
[0067] Example 5
[0068] Preparation of MoO3 / g-C3N4: 34mg MoO3 and 4g dicyandiamide were added to a beaker containing 30mL deionized water, and the beaker was placed in a 50℃ water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80℃ until the water was completely removed to obtain a solid, and then the solid was dried in a 70℃ oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and heated to 500℃ at a heating rate of 2-10℃ / min and kept at a constant temperature for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named MoO3 / g-C3N4.
[0069] Preparation of g-C3N4(MoO3): Take 4mL of 25wt.%NH3•H2O and dissolve it in 20mL of distilled water. Grind the MoO3 / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove MoO3, then centrifuge and dry. The obtained yellow powder is named g-C3N4(MoO3).
[0070] Preparation of catalyst Pt / g-C3N4(MoO3): Pt nanoparticles were loaded on the prepared g-C3N4(MoO3) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(MoO3) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PtCl4 aqueous solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PtCl4 was reduced to Pt under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The black powder obtained by centrifugation was named Pt / g-C3N4(MoO3).
[0071] Example 6
[0072] Preparation of MoO3 / g-C3N4: 47 mg of ammonium molybdate solid powder and 4 g of dicyandiamide were added to a beaker containing 30 mL of deionized water, and the beaker was placed in a 50°C water bath and stirred for 1 hour to fully mix the template and dicyandiamide, and then the water bath was heated to 80°C until the water was completely removed to obtain a solid, and then the solid was dried in a 70°C oven for 12 hours. The dried sample was taken out, fully ground for 15 minutes, and then transferred to a muffle furnace, and heated to 500°C at a heating rate of 2 to 10°C / min and kept at a constant temperature for 4 hours. After the muffle furnace was naturally cooled to room temperature, the sample was taken out, and the obtained gray powder was named MoO3 / g-C3N4.
[0073] Preparation of g-C3N4(MoO3): Take 4mL of 25wt.% NH3·H2O and dissolve it in 20mL of distilled water. Grind the MoO3 / g-C3N4 obtained after calcination thoroughly and add it to the above solution. Stir for 12 hours to remove MoO3, then centrifuge and dry. The obtained yellow powder is named g-C3N4(MoO3).
[0074] Preparation of catalyst Pd / g-C3N4(MoO3): Pd nanoparticles were loaded on the prepared g-C3N4(MoO3) carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4(MoO3) carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PdCl2 ammonia solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PdCl2 was reduced to Pd under the action of NaBH4. 0 The mixture was stirred for 2 hours and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pd / g-C3N4(MoO3)-M (M represents a catalyst prepared with ammonium molybdate as a precursor).
[0075] Comparative Example 1
[0076] Preparation of g-C3N4: Grind 4 g of dicyandiamide thoroughly for 15 minutes and transfer it to a muffle furnace. Heat the temperature to 500°C at a heating rate of 5°C / min and keep the temperature constant for 4 hours. After the muffle furnace cools naturally to room temperature, take out the sample and the obtained gray powder is named g-C3N4.
[0077] Preparation of catalyst Pd / g-C3N4: Pd nanoparticles were loaded on the prepared g-C3N4 carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4 carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PdCl2 ammonia solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PdCl2 was reduced to Pd under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pd / g-C3N4.
[0078] Comparative Example 2
[0079] Preparation of g-C3N4: Grind 4 g of dicyandiamide thoroughly for 15 minutes and transfer it to a muffle furnace. Heat the temperature to 500°C at a heating rate of 5°C / min and keep the temperature constant for 4 hours. After the muffle furnace cools naturally to room temperature, take out the sample and the obtained gray powder is named g-C3N4.
[0080] Preparation of catalyst Ru / g-C3N4: Ru nanoparticles were loaded on the prepared g-C3N4 carrier by a simple impregnation method. The specific preparation process is as follows: 0.2 g of g-C3N4 carrier was added to a single-necked flask containing 20 mL of distilled water and 4 mL of 1 g / L RuCl3 aqueous solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that RuCl3 was reduced to Ru under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Ru / g-C3N4.
[0081] Comparative Example 3
[0082] Preparation of g-C3N4: Grind 4 g of dicyandiamide thoroughly for 15 minutes and transfer it to a muffle furnace. Heat the temperature to 500°C at a heating rate of 5°C / min and keep the temperature constant for 4 hours. After the muffle furnace cools naturally to room temperature, take out the sample and the obtained gray powder is named g-C3N4.
[0083] Preparation of catalyst Pt / g-C3N4: Pt nanoparticles were loaded on the prepared g-C3N4 carrier by a simple impregnation method. The specific preparation process is as follows: 0.2g of g-C3N4 carrier was added to a single-necked flask containing 20mL of distilled water and 4mL of 1g / L PtCl4 aqueous solution, and stirred for 1 hour. Then, an excess of NaBH4 aqueous solution was added dropwise, and the solution quickly turned black, indicating that PtCl4 was reduced to Ru under the action of NaBH4. 0 The stirring was continued for 2 hours, and then centrifuged. During the centrifugation, the solution was washed with distilled water until it was neutral. The gray powder obtained by centrifugation was named Pt / g-C3N4.
[0084] Test Case
[0085] (1) The catalysts prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to X-ray photoelectron spectroscopy testing, wherein: Figure 1 The X-ray photoelectron spectrum of the catalyst of Example 1 is shown. Figure 1 As shown, Figure 1 The characteristic peaks at 340.1 and 334.9 eV in (d) are attributed to Pd 0 3d 3 / 2 and Pd 0 3d 5 / 2 , the characteristic peaks at 341.0 and 335.7 eV are attributed to Pd 2+ 3d 3 / 2 and Pd 2+ 3d 5 / 2 , the characteristic peaks at 342.8 and 337.7 eV are attributed to Pd-N x 3d 3 / 2 and Pd-N x 3d 5 / 2 , which proves that Pd-N is formed in the catalyst of the present application x Active center.
[0086] The X-ray photoelectron spectroscopy of Example 2-6 also shows that Pd-N is formed in the catalyst. x Active center, while no Pd-N x 、Pt-N x 、Ru-N x characteristic peaks, without forming precious metal-N x Active center.
[0087] (2) The catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were used in the hydrogenation reaction of p-nitrophenol. The reaction conditions were: 10 mg of the catalyst was added to 50 mL of a 2 mmol / L 4-nitrophenol solution, H2 was introduced at a rate of 30 mL / min, the reaction was carried out at normal pressure for 60 min, and the conversion rate of the reactants was tested. The data obtained were as follows:
[0088] Table 1
[0089]
[0090]
[0091] According to the test results in Table 1, the catalysts prepared in Examples 1 to 6 contain metal-N x Active center, Comparative Examples 1 to 3 did not use metal oxides as templates, and the prepared catalysts could not form metal-N x The conversion rates of the catalysts in Examples 1 to 6 are greatly improved compared to those in Comparative Examples 1 to 3, indicating that the catalysts prepared in the present application have excellent catalytic effects in hydrogenation reactions.
[0092] (3) The catalyst prepared in Example 1 was used in the hydrogenation reaction of other nitrobenzene series. The reaction conditions were: 10 mmol of the reactant was dissolved in 10 mL of ethanol, 10 mg of the catalyst was added to the solution, H2 was introduced at 70°C for reaction, and the reaction pressure was 1 MPa. The conversion rate of the reactant obtained by testing is shown in the following table:
[0093] Table 2
[0094]
[0095] In summary, the metal-N prepared by the present invention x The active center catalyst has good catalytic performance. When the noble metal loading is 1wt.%, the conversion rate of nitrobenzene series can reach more than 99%. It has high catalytic activity and long service life.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.
Claims
1. A metal - N x A catalyst, characterized in that The catalyst comprises a carrier and a noble metal loaded on the carrier, wherein the carrier is g-C3N4, and the catalyst contains a noble metal-N x Active center.
2. The catalyst according to claim 1, characterized in that The noble metal is one or more of Pt, Pd, Ru, Ag, and Rh; Preferably, the loading amount of the noble metal is 0.5 to 5 wt.%, preferably 0.8 to 1.2 wt.%, of the total mass of the catalyst.
3. The catalyst according to claim 1 or 2, characterized in that The preparation method of the catalyst comprises the steps of mixing and calcining dicyandiamide and a metal oxide and / or a metal salt precursor to prepare a carrier, and then loading a noble metal onto the carrier.
4. Metal-N x The method for preparing a catalyst is characterized in that: The following steps are involved: (1) mixing a metal oxide and / or metal salt precursor with a dicyandiamide solution and calcining to obtain a powder; (2) contacting the powder obtained in step (1) with an acid solution or an alkali solution to obtain a carrier; (3) Loading the noble metal on the carrier to obtain a metal-N x catalyst.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the dicyandiamide to the metal oxide and / or metal salt precursor is (100-400):1; Preferably, the noble metal is one or more of Pt, Pd, Ru, Ag, and Rh; Preferably, the loading amount of the noble metal is 0.5 to 5 wt % of the total mass of the catalyst, preferably 0.8 to 1.2 wt %.
6. The preparation method according to claim 4 or 5, characterized in that: The metal oxide is selected from one or more of MoO3, WO3, ZnO, MnO2, SiO2, TiO2; and / or The metal salt precursor is one or more of ammonium molybdate, ammonium tungstate and zinc acetate.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (1), the mixing time is 0.5 to 2 hours and the temperature is 40 to 60° C.; and / or The calcination conditions include: calcination temperature of 400-600°C, calcination time of 3-5h, heating rate of 2-10°C / min; and / or In step (2), the pH value of the acid solution is 2-4, or the pH value of the alkali solution is 8-10.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the noble metal is loaded by impregnation, preferably by equal volume impregnation or excess impregnation; Preferably, the impregnation method comprises mixing a noble metal salt solution with a carrier and then adding a reducing agent for reduction; Preferably, the noble metal is metal nanoparticles.
9. A hydrogenation reaction, characterized in that The hydrogenation reaction is carried out under the catalysis of the catalyst described in any one of claims 1 to 3 or the catalyst prepared by the preparation method described in any one of claims 4 to 8.
10. The hydrogenation reaction according to claim 9, characterized in that The hydrogenation reaction is to hydrogenate nitrobenzene to prepare aminobenzene. Preferably, the conditions of the hydrogenation reaction preferably include: The reaction temperature is 25-35°C, the reaction time is 0.8-1.2h, and the reaction pressure is 0.98-0.12MPa.
Citation Information
Patent Citations
Formic acid synthesis catalyst and preparation and application thereof
CN106861737A
Catalyst applied to continuous hydrogenation of aromatic nitro compound and preparation method
CN114289050A